The bacterial contamination of food handlers hands in Wad madani city restaurants, Sudan - Honua, Mohanad Hassan Mohamed (International Journal Of Community Medicine And Public Health, 2018)
Background: Food handlers may cross-contaminate raw and processed food stuffs as well as inadequately cook and store foods. These contributory factors are due to a lack of food hygiene awareness or implementation. Methods: Study was conducted between (October to December 2017), 100 samples were collected randomly from hands of food handlers working in restaurants of Wad Madani city. A sterile quality swabs were used to collecting the samples from handlers after screened the hand of handler particularly around the fingers and palm. The swab was immediately sealed and transported to Al-bagea medical center laboratory for examination. One hundred questionnaires were designed to obtain information about food handlers knowledge and their personal hygiene. The data was analyzed by (SPSS v16th) system. Results: The contaminated hands of food handlers by bacteria was 87%, the minimum colony forming unit (CFU) was (10×106 cfu/ml), 70% of handlers were educated and 55% of handlers were working in restaurants more than 5 years. Conclusions: The study showed high level of education of food handlers and may be aware of the need for personal hygiene, they do not comprehend crucial aspects of hygiene such as cleaning of work surfaces and washing their hands by water and soap, so we need deep messages for health education of food handlers.